2005
DOI: 10.1111/j.1439-0507.2005.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of chromomycosis caused by Fonsecaea pedrosoi and a review of reported cases of dematiaceous fungal infection in Japan

Abstract: We report a case of chromomycosis caused by Fonsecaea pedrosoi that developed in the left buttock of a 63-year-old female farmer. About 4 years ago, the patient developed erythema in the left buttock, which gradually spread. At the first consultation, we noted a well-defined, red-brown, infiltrated erythematous plaque (8 x 6 cm). Histopathological examination revealed a granulomatous lesion, containing sclerotic cells, associated with giant cells in the upper dermis. The causative fungus was difficult to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 6 publications
0
40
0
2
Order By: Relevance
“…The first Japanese case was described in 1930 by Kano, who reported a female patient with an unusual CBM-like infection in the facial region, caused by Hormiscium dermatitidis (currently Exophiala dermatitidis) (130). Since the first description, several Japanese authors reported ϳ700 cases of CBM infections (130)(131)(132)(133). Several hundred cases have been reported from Mainland China since the first description by Yew in 1951 (134,135).…”
Section: Chromoblastomycosis In Asia and Oceaniamentioning
confidence: 99%
“…The first Japanese case was described in 1930 by Kano, who reported a female patient with an unusual CBM-like infection in the facial region, caused by Hormiscium dermatitidis (currently Exophiala dermatitidis) (130). Since the first description, several Japanese authors reported ϳ700 cases of CBM infections (130)(131)(132)(133). Several hundred cases have been reported from Mainland China since the first description by Yew in 1951 (134,135).…”
Section: Chromoblastomycosis In Asia and Oceaniamentioning
confidence: 99%
“…In Japan about 10 cases of CBM are reported annually. The occurrence rate of individual species in the last two decades of the 20 th century was as follows: F. pedrosoi – 71%, E. jeanselmei – 20%, Phialophora verrucosa – 4.5%, Exophiala dermatitidis – 2% [49]. …”
Section: Geographical Distributionmentioning
confidence: 99%
“…It was first reported from India in 1957 by Thomas et al [1] Other than India and Brazil, Chromoblastomycosis has been reported from Madagascar, Sri Lanka, West Central Africa, Japan, Mexico, Cuba, Dominican Republic, Nepal, Australia, and Venezuela. [2][3][4][5][6][7][8][9][10][11][12][13][14] According to one report, Madagascar represents the most important focus of this fungal disease. [7] Brazil is another country reporting large number of cases.…”
Section: Discussionmentioning
confidence: 99%